Adaptation of a freshwater evaluation framework to a coastal system: The case of Kamari, Santorini. (15th June 2021) - Ćulibrk, Alexandra; Tzoraki, Ourania; Portman, Michelle E.
Abstract: The erosion of sandy beaches creates a significant impact on the local society, the economy and the environment. The present study is an attempt to adapt the innovative DESSIN (Demonstrate Ecosystem Services Enabling Innovation in the Water Sector) framework that specializes in freshwater applications, to urban coastal systems. The framework is applied in the case of Kamari beach, Santorini (Greece), to assess the sustainability of all possible anti-erosion measures. To identify the most vulnerable parts of the coastline, the study used two sensitivity indices: the Coastal Vulnerability Index (CVI), and the Socioeconomic Index (SocCVI). A supply-demand model was applied for the integration of all three aspects that characterize the system: social, economic, and environmental. To project the impact of erosion in the future, the system's state was analyzed in three steps a) the present, b) after the installation of the coastal protection measures and c) a scenario where no protection actions were taken (RCP4.5 scenario). In the current situation the most susceptible part of the coastline due to anthropogenic and environmental pressures is the central one, which does not immediately affect the socio-economic activities of the urban area. In contrast, future changes brought about by climate change will endanger the system's equilibrium and anti-erosion actions are necessary. With the application of the adapted DESSIN framework, the combined installation of submerged breakwaters with sediment replacement is the most sustainable action, promoting socio-economic growth and the protection of essential ecosystem services. Graphical abstract: Image 1 Highlights: Beyond freshwater bodies, DESSIN framework could be applied to coastal studies. DESSIN's flexible structure makes it possible to adapt it to coastal systems. The Demand-Supply model is a useful tool to summarize all aspects of these systems. Currently Kamari's socio-economic activities are not affected by the erosion. The main pressure on the beach is due the morphology and seas hydrodynamics.